The Perils of Non-State Actors in Pakistan: Assessing the Risks of Nuclear Safety and Security - Iftikhar Ali; Muhammad Sadiq (International Journal of Nuclear Security, 2023)
Pakistan is facing security problems on multiple fronts, including economic default, social fragmentation, poor civil–military relations, political polarization, and environmental degradation. However, the biggest security threat comes from non-state actors (NSAs) and terrorism. Using empirical evidence, this research paper evaluates the risk of nuclear terrorism by NSAs in Pakistan. It adopts an interpretive approach to examine international concerns regarding nuclear security in Pakistan. The study focuses on the potential for technology and weapon-usable materials to fall into the hands of violent NSAs. It concludes that, despite ongoing security challenges, Pakistan has taken steps to strengthen its legislative and institutional measures to protect its nuclear infrastructure.
Keywords: Non-State Actors; Nuclear Terrorism; Safety; Secuity